Die Familienkiste, Band 1: Mensch-Objekt-Beziehungen im Mittelalter und in der Renaissance - Antenhofer, Christina (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Golden crowns, precious relics or rare gifts - it is such treasures that we paradigmatically associate with the Middle Ages, while we think of the Modern Age as the beginning of consumer culture and collections. This book starts from this dichotomy and tells a different story of material culture of the Middle Ages and the Renaissance, in which not the things are at the heart of interest but their capacity to build relationships. In the metaphor of the family chest the book captures the meaning that objects have for individuals and families across generations, times and spaces, while it writes a cultural history of administration that offers new perspectives on changes and continuities in the handling of objects until the present.Volume 1: https://e-book.fwf.ac.at/o:1721Volume 2: https://e-book.fwf.ac.at/o:1722